2014
DOI: 10.1186/1746-4269-10-18
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal plants used to treat human ailments in the prehistoric place of Harla and Dengego valleys, eastern Ethiopia

Abstract: BackgroundTraditional medicines remained as the most affordable and easily accessible source of treatment in the primary health care system among diverse communities in Ethiopia. The Oromo community living in the prehistoric Harla and Dengego valleys has long history of ethnomedicinal know-how and practice against human and livestock ailments. However, this rich ethnomedicinal knowledge had been remained unexplored hitherto. This study focus on the comprehensive ethnomedicinal investigation in an attempt to sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 33 publications
7
62
0
Order By: Relevance
“…Differences in medicinal plants knowledge among age groups was also reported in other studies (Gebrezgabiher et al, 2013;Tamiru et al, 2013;Yigezu et al, 2014;Chekole et al, 2015;Tugume et al, 2016). This might be attributed to the current expansion of education and health centers to kebele level which has resulted in the young generation focusing on modern medicines (Belayneh and Bussa, 2014) and advancement in science and technology has changed the social values and therefore, transformed the younger generation at a faster rate into the new tradition (Awas, 2007;Murad et al, 2013).…”
Section: Characteristics Of Respondentssupporting
confidence: 66%
See 2 more Smart Citations
“…Differences in medicinal plants knowledge among age groups was also reported in other studies (Gebrezgabiher et al, 2013;Tamiru et al, 2013;Yigezu et al, 2014;Chekole et al, 2015;Tugume et al, 2016). This might be attributed to the current expansion of education and health centers to kebele level which has resulted in the young generation focusing on modern medicines (Belayneh and Bussa, 2014) and advancement in science and technology has changed the social values and therefore, transformed the younger generation at a faster rate into the new tradition (Awas, 2007;Murad et al, 2013).…”
Section: Characteristics Of Respondentssupporting
confidence: 66%
“…Of the total 52 medicinal plants collected from the study area, 23 species (44%) were shrubs followed by 19 species (37%) herbs and 10 species ( Mesfin et al, 2009;Belayneh and Bussa, 2014) where shrubs and herbs are the largest plant growth habits.…”
Section: Habit Of the Medicinal Plantmentioning
confidence: 99%
See 1 more Smart Citation
“…Leach, locally called ‘Eret’, is among the endemic Aloe species of Ethiopia, which has been described in 1971 in an area between the cities of Bahir Dar and Gonder in the northern part of the country. Like many other Aloe species found in Ethiopia with ethnomedicinal applications [15, 16], the local people extensively use the leaves of A. trigonantha for the treatment of infectious and inflammatory diseases [17]. However, despite its use in traditional medicine and possible therapeutic applications, no phytochemical or biological studies carried out on the plant could be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The plant parts were harvested and prepared in different methods according to the plant part used and the disease to be treated. Exploitation of different plant parts for medicinal purposes is corroborated by scientists who attest that plant parts such as leaves, roots, bark and fruits are the major plant parts exploited to make curative medicine (Ahmad et al, 2014;Belayneh and Bussa, 2014;Lawal et.al., 2014).…”
Section: The Plant Parts Harvested To Make Plant-derived Medicinementioning
confidence: 99%